SUSTAINABLE TRANSPORT AND PASSENGER TRANSPORT IN A LONG-DISTANCE COMMUNICATION - Pshinko, O. M.; Barash, Yu. S.; Verkhohlyadova, N. I.; Korzhenevych, I. P.; Logvynenko, A. V.; Loboiko, L. M. (Science and Transport Progress, 2008)
The model of basic factors, which should be taken into account for the strategic planning of far-distant passenger transportation, is considered from the positions of sustainable development.